Contribution of Land Water Storage Change to Regional Sea-Level Rise Over the Twenty-First Century - Karabil, Sitar; Sutanudjaja, Edwin H.; Lambert, Erwin; Bierkens, Marc F. P.; Van de Wal, Roderik S. W. (Frontiers in Earth Science, 2021)
Change in Land Water Storage (LWS) is one of the main components driving sea-level rise over the twenty-first century. LWS alteration results from both human activities and climate change. Up to now, all components to sea-level change are usually quantified upon a certain climate change scenario except land water changes. Here, we propose to improve this by analyzing the contribution of LWS to regional sea-level change by considering five Coupled Model Intercomparison Project Phase 5 (CMIP5) climate models forced by three different Representative Concentration Pathway (RCP) greenhouse gas emission scenarios. For this analysis, we used LWS output of the global hydrological and water resources model, PCR-GLOBWB 2, in order to project regional sea-level patterns. Projections of ensemble means indicate a range of LWS-driven sea-level rise with larger differences in projections among climate models than between scenarios. Our results suggest that LWS change will contribute around 10% to the projected global mean sea-level rise by the end of twenty-first century. Contribution of LWS to regional sea-level rise is projected to be considerably larger than the global mean over several regions, up to 60% higher than global average of LWS-driven sea-level rise, including the Pacific islands, the south coast of Africa and the west coast of Australia.